Back to the dirt - Bill, Frank, 1974- (FSG Originals / Farrar, Straus and Giroux, 2023)
"Frank Bill, the author of Crimes in Southern Indiana, is back with a gritty, wrenching novel from deep inside the traumas of a broken American heartland"--